THE EFFECT OF PERCEIVED EASE OF USE ON INTENTION TO USE ON BANK SYARIAH INDONESIA MOBILE BANKING USERS IS MEDIATED BY E-TRUST AND RELIGIOSITY AS MODERATORS - Dennis Shabri Alfani; Agung Yuniarto M.S; Radityo Putro Handrito (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The increase in smartphone users has driven customer demand for mobile banking services, so that many banks have offered innovative banking services to expand the reach of their customers who have accounts or those who do not have bank accounts. Banking is developing the use of mobile banking as a demand to meet the increasing transaction needs of individuals and companies. This is supported by advances in technology, especially cellular telecommunication. Research on "The Influence of Perceived Ease of Use on Behavioral Intention is mediated by E-Trust and Religiosity as moderators of Bank Syariah Indonesia mobile banking users" using a quantitative approach. This study explains the influence between Perceived ease of use on behavioral intention with religiosity and trust as mediating variables. This study uses the PLS analysis technique. Based on the findings of this study, it has been found that religiosity as measured by belief, experiential, considering the benefit of using a product, and carrying out activities in accordance with Islamic teachings is confirmed not to affect customer confidence in the intention to use BSI Mobile. The results of this study also show that perceived ease of use has a significant or important impact on behavioral intention through e-trust. The impact of e-trust mediation is complete mediation. When the perceived ease of use offered by BSI is assessed as lacking by the user, the user will not use the application. Therefore it is bridged by the mediating effect of the e-trust variable. In this case BSI must be able to guarantee all the security and personal data of customers, maintain the credibility of the company and reach and realize the positive expectations of its users for BSI Mobile. Perceived Ease of Use on Behavioral Intention through E-Trust. E-Trust has a partial mediation role on the effect of Perceived ease of use on behavioral intention. It means, perceived ease of use can influence behavioral intention directly or indirectly through trust. Banking mobile banking application providers need to improve strategies in increasing customer trust in BSI Mobile so that there will be continuous use of the application system.